Analisis Peranan Pemerintah terhadap Pertumbuhan Ekonomi Kabupaten-Kota di Jawa Timur Tahun 2009-2014 - Napitupulu, Henny Widya Anita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Economic growth is the change of better economic conditions of a region within a certain period. This study aims to determine the effect of government spending, investment, labor force, and HDI (education index and health index) on economic growth in City-district,East Java and government enrole in the fourth aspect (government expenditure, investment, labor force, and HDI) of economic growth. The results from this study is that government expenditure variable and HDI (education and health indices) have a significant effect on economic growth of District, East Java, while the variable investment and labor force does not have a significant effect on economic growth City-district of East Java. HDI (Human Development Index) became the most dominant factor influencing economic growth as a representation of the quality of human resources in production activities. The region that affected most by the fourth aspect is Surabaya, and the region that affected smallest is Blitar. The Government can take role and increase government expenditure aspect, especially government expenditure on investment, hence labor force can be absorbed more then HDI will increase which is applied in areas (City-District) with economic growth low levels like Mojokerto and Blitar.Â Keywords: Economic Growth, government expenditure, investment, labor force, HDI, Government enrole